The New General Anti-Avoidance Rule: A comprehensive discourse on this Statute - Izak, Daniel Petrus Louw (Department of Commercial Law, 2014)
On 3 November 2005, the Minister of Finance explicitly recognised the need for a revised GAAR stating: 'What we can't accommodate is a rule which is intended to limit avoidance that is so abused and tatty with wear.' This paved the way for the SARS launching their 2005 discussion paper on GAAR. SARS, in their introduction, discussed and pointed out the ramifications of aggressive tax avoidance structures. SARS held further that not only do such structures, inter alia, affect the short-term revenue loss of the fiscus, but also influence the economy negatively from a longerterm perspective and weaken National Treasury's ability to successfully implement and govern economic policy. The result - the much-anticipated new GAAR measures, incorporated in twelve new sections of the Act, viz sections 80A - 80L, which came into effect for schemes or arrangements entered into, on, or after 2 November 2006.